2015
DOI: 10.1177/1933719114553064
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Urinary Cytokeratin 19 Fragment for Endometriosis

Abstract: Endometriosis affects up to 10% of women of reproductive age and 176 million women worldwide. The prevalence in women with infertility is between 30% and 50% but may be higher in women with pelvic pain, interstitial cystitis, or irritable bowel syndrome. Cytokeratin 19 has been suggested as a potential biomarker in urine for the diagnosis of this condition. The objective of this study was to prospectively determine the accuracy and the performance of a urinary cytokeratin 19 (uCYFRA 21-1) test for diagnosing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
9
1
1
Order By: Relevance
“…Both studies concluded that CK 19 was not altered by the presence of endometriosis and that their levels were not a ected by menstrual cycle phases (Kuessel 2014), by severity of the disease or when the levels were normalised to urine creatinine or urine protein (Lessey 2014). Only one of these studies (98 participants, cycle phase not reported, rASRM I-IV) evaluated the diagnostic accuracy of uCYFRA 21-1 (Lessey 2014), demonstrating a very low sensitivity of 0.11 (95% CI, 0.05 to 0.22) with a high specificity 0.94 (95% CI, 0.81 to 0.99), using a chosen cut-o of more than 5.3 ng/ml (Figure 9). This evidence suggests that the cytokeratin 19 molecule is not reliable as a diagnostic test for endometriosis, but further testing is required to confirm or refute these findings.…”
Section: ) Cytokeratin-19 Fragments (Ucyfra 21-1)mentioning
confidence: 99%
See 2 more Smart Citations
“…Both studies concluded that CK 19 was not altered by the presence of endometriosis and that their levels were not a ected by menstrual cycle phases (Kuessel 2014), by severity of the disease or when the levels were normalised to urine creatinine or urine protein (Lessey 2014). Only one of these studies (98 participants, cycle phase not reported, rASRM I-IV) evaluated the diagnostic accuracy of uCYFRA 21-1 (Lessey 2014), demonstrating a very low sensitivity of 0.11 (95% CI, 0.05 to 0.22) with a high specificity 0.94 (95% CI, 0.81 to 0.99), using a chosen cut-o of more than 5.3 ng/ml (Figure 9). This evidence suggests that the cytokeratin 19 molecule is not reliable as a diagnostic test for endometriosis, but further testing is required to confirm or refute these findings.…”
Section: ) Cytokeratin-19 Fragments (Ucyfra 21-1)mentioning
confidence: 99%
“…Each study evaluated one or several biomarkers. Most studies reported diagnostic estimates for biomarkers that demonstrated di erential expression between women with and without endometriosis, although in one publication this assessment was undertaken for a test that demonstrated no di erential expression (Lessey 2014). In three studies there was no di erence in the expression between the women with and without endometriosis and the diagnostic test accuracy of the urinary biomarker was not evaluated (n = 208 participants, median 70, range 62 to 76 women).…”
Section: Basic Features Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study included eight studies, five of which evaluated the diagnostic performance of four urine biomarkers for endometriosis. Results showed that three biomarkers (non-neuronal enolase, [ 48 ] vitamin D binding protein, [ 49 ] and urinary peptide profiling [ 50 , 51 ] ) can better distinguish women with or without endometriosis while cytokeratin 19 [ 52 ] showed no significant difference. Overall, none of the urinary biomarkers mentioned above met the criteria for a replacement test or a triage test though several urine biomarkers may have diagnostic potential and further evaluation is still required before the introduction of routine clinical practice.…”
Section: Othersmentioning
confidence: 99%
“…A valid analysis of the results of these studies is not possible due to these methodological errors. Finally, we refer to a recent publication by Lessey et al 35 who measured the CYFRA 21-1 levels in relation to creatinine. The cycle phases were not used, which is probably due to the fact that the patient samples dated back to the year 2011 and the cycle phases were not yet considered at that time.…”
Section: Discussionmentioning
confidence: 99%